2021
DOI: 10.3389/fmed.2021.639441
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Hereditary TTP Caused by Homozygosity for a Rare Complex ADAMTS13 Allele After Salmonella Infection in a 43-Year-Old Asylum Seeker

Abstract: A 43-year-old Armenian patient was diagnosed with salmonella infection and thrombotic microangiopathy (TMA). The clinical course was benign with resolution of all laboratory alterations after antibiotic treatment. Constantly deficient ADAMTS13 activity without ADAMTS13 inhibitors and evidence of homozygosity for a rare complex ADAMTS13 allele led to the diagnosis of congenital thrombotic thrombocytopenic purpura (cTTP). Half-life of ADAMTS13 after plasma infusion was calculated (27,6h) and double blinded plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
2
0
2
Order By: Relevance
“…All eight S. Typhimurium type strains carried norV gene, and both norV gene and FlRd protein had high identity compared to S. Typhimurium_zhang and TW14359. Moreover, cTTP cases have previously been reported with S. enterica infection (Wendt et al, 2021); therefore, the norV and FlRd of 73 S. enterica and S. Typhimurium_zhang were also compared, which revealed that norV and FlRd in most S. enterica had high identity with S. Typhimurium_zhang. These results indicate that norV is possibly linked to high morbidity of patients with TTP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All eight S. Typhimurium type strains carried norV gene, and both norV gene and FlRd protein had high identity compared to S. Typhimurium_zhang and TW14359. Moreover, cTTP cases have previously been reported with S. enterica infection (Wendt et al, 2021); therefore, the norV and FlRd of 73 S. enterica and S. Typhimurium_zhang were also compared, which revealed that norV and FlRd in most S. enterica had high identity with S. Typhimurium_zhang. These results indicate that norV is possibly linked to high morbidity of patients with TTP.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, infection-induced TTP has been reported with shiga toxin-producing Escherichia coli, hepatitis A virus, dengue virus, influenza virus, and SARS-CoV-2 (Thrombotic Thrombocytopenic Purpura Associated With Escherichia Coli O157: H7-Washington, 1986;Bitzan and Zieg, 2018;Albiol et al, 2020;Gogireddy et al, 2020;Beaulieu et al, 2021;Montgomery et al, 2021). Previous research has revealed that congenital TTP (cTTP) can be triggered by S. enterica infection (Wendt et al, 2021). To the best of our knowledge, acquired TTP induced by S. enterica serovar Typhimurium (hereafter, S. Typhimurium) has not been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…Neben den klinischen Zeichen der Organdysfunktion ist die TMA charakterisiert durch eine Thrombozytopenie, eine mikroangiopathische Hämolyse (coombs-negative hämolytische Anämie mit erhöhter LDH und erniedrigtem Haptoglobin) sowie als Zeichen der mechanischen Schädigung der Erythrozyten eine variable Anzahl an Fragmentozyten (mechanisch geschädigte "fragmentierte" Erythrozyten). Bei TTP-Fällen ohne Nachweis von ADAMTS13-Antikörpern muss immer, selbst bei älteren Patienten [2], an eine hereditäre Form der TTP (hTTP) gedacht werden und eine Mutationsanalyse im ADAMTS13-Gen veranlasst werden.…”
unclassified
“…Bei TTP-Fällen ohne Nachweis von ADAMTS13-Antikörpern muss immer, selbst bei älteren Patienten [2], an eine hereditäre Form der TTP (hTTP) gedacht werden und eine Mutationsanalyse im ADAMTS13-Gen veranlasst werden.…”
unclassified